1990
DOI: 10.1111/j.1539-6924.1990.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Uptake of Organic Chemicals from a Soil Matrix

Abstract: Uptake of chemicals from soil on human skin is considered. Based on a review of literature on the structure of human skin, the processes by which chemicals pass through this boundary, and experiments that reveal the rate and magnitude of this transport process; a two-layer model is presented for estimating how chemical uptake through the stratum corneum depends on chemical properties, skin properties, soil properties and exposure conditions. The model is applied to two limiting scenarios--(1) continuous deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In contrast to liquid absorption, the dermal uptake of benzene from contaminated soil has been modeled by McKone et al (213) and Burmaster et al (214). They showed that benzene is poorly absorbed from a soil matrix and that even under ideal conditions (extensive contact for long periods of time), less than 10% of benzene in soil will be absorbed by the skin.…”
Section: Human Exposure Dermal Uptakementioning
confidence: 99%
“…In contrast to liquid absorption, the dermal uptake of benzene from contaminated soil has been modeled by McKone et al (213) and Burmaster et al (214). They showed that benzene is poorly absorbed from a soil matrix and that even under ideal conditions (extensive contact for long periods of time), less than 10% of benzene in soil will be absorbed by the skin.…”
Section: Human Exposure Dermal Uptakementioning
confidence: 99%
“…Approaches developed for OP insecticide exposure (Sedman 1989, McKone 1990, Iwata et al 1977, as well as some others) require data that are unavailable for VX and sulfur mustard…”
Section: Dermal Exposure To Soilmentioning
confidence: 99%
“…Exposure estimates are affected by uncertainties in pathway exposure factors (PEFs - McKone, 1990). PEFs are terms that translate unit concentrations in media (e.g., pCi per L) and food chain components into exposures per unit time (exposure rates).…”
Section: Introductionmentioning
confidence: 99%
“…PEFs are terms that translate unit concentrations in media (e.g., pCi per L) and food chain components into exposures per unit time (exposure rates). PEFs use information on human physiology and behavior, and environmental transport for specific media (McKone, 1990). These uncertainties arise from biological and behavioral variations, as well as the accuracy and precision of the estimated values for each parameter.…”
Section: Introductionmentioning
confidence: 99%